ANALISIS UMUR SIMPAN GULAI AYAM NANAS KEMASAN KALENG BERBASIS PROYEK IMPLEMENTASI KURIKULUM MERDEKA (IKM): Anita Ekawati*, Muhammad Dzaky Alif, Dwina Ananda Zakirah - Anita Ekawati; Muhammad Dzaky Alif; Dwina Ananda Zakirah (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2023)
IKM implements project-based learning that supports 21st-century skills, namely character development according to the profile of Pancasila students, one of which is by utilizing the science laboratory as a place for activities in research and education. Project-based learning can be linked by students to the regional potential of Lahat Regency, South Sumatra Province, one of which is Pineapple Chicken Curry which is food made from free-range chicken or other chicken meat and combined with pineapple and seasoned coconut milk sauce. Along with the times, pineapple chicken curry has now been innovated in cans. The purpose was to analyze canned pineapple chicken curry in the application of IKM project learning through the Accelerated Shelf-Life Testing (ASLT) method. Analysis of the expiration date of canned chicken curry if it is carried out in a curriculum realization project. It can be seen higher the storage temperature of pineapple chicken, the shorter the shelf life product. The Arrhenius approach yields rocker samples with a shelf life of 0.44 months, 0.49 months, and 0.46 months temperature in 25°C, 35°C and 45°C. Higher storage temperature, higher degree of deterioration (k).